Application of electrospun polyacrylonitrile/Zn-MOF-74@GO nanocomposite as the sorbent for online micro solid-phase extraction of chlorobenzenes in water, soil, and food samples prior to liquid chromatography analysis. (30th November 2021) - Amini, Shima; Ebrahimzadeh, Homeira; Seidi, Shahram; Jalilian, Niloofar
Highlights: An online µSPE procedure was developed for the extraction of chlorobenzenes. A novel electrospun composite of polyacrylonitrile/Zn-MOF-74@GO was prepared. Zn-MOF-74@GO improved the extraction efficiency of electrospun nanofibers. The proposed method is fast and eco-friendly due to the low solvent consumption. Abstract: An online micro solid-phase extraction (online-µSPE) using electrospun nanofibers, as an efficient sorbent, was developed to extract chlorobenzenes (CBs) from paddy soil, agricultural wastewater, and food samples (fruit juices, vegetables, rice samples) followed by high performance liquid chromatography analysis. Electrospun nanofibers were fabricated using a nanocomposite containing polyacrylonitrile and Zn-metal organic framework 74 @graphene oxide (PAN/Zn-MOF-74@GO), and subsequently characterized. Under the optimal conditions, acceptable linearity was obtained in the range of 0.25–700.00 ng mL −1 for 1, 2-dichlorobenzene (1, 2-DCB) and 2.50–700.00 ng mL −1 for both 1, 2, 3-trichlorobenzene (1, 2, 3-TCB) and 1, 2, 4-trichlorobenzene (1, 2, 4-TCB) with determination coefficients ≥ 0.9991. The limits of detection ranged from 0.08 to 1.10 ng mL −1 . The intra-day and inter-day single fiber and fiber to fiber relative standard deviations were observed in the range of 4.1%–9.5% and 5.8%–12.1%, respectively. The performance of this method was examined by determining the target analytes in the different spiked samples.